Olive oil by-product as functional ingredient in bakery products. Influence of processing and evaluation of biological effects. (May 2020) - Di Nunzio, Mattia; Picone, Gianfranco; Pasini, Federica; Chiarello, Elena; Caboni, Maria Fiorenza; Capozzi, Francesco; Gianotti, Andrea; Bordoni, Alessandra
Graphical abstract: Highlights: The magnitude of the increase in phenols due to olive pomace is not proportional to the biological effect. Bioactive bioaccessibility is an important determinant of food functionality and it is modulated by processing. Bread-making procedures must be carefully modulated based on ingredients. At tested concentration polyphenols do not modulate metabolome in Caco-2 cells. Abstract: Nowadays, the strong demand for adequate nutrition is accompanied by concern about environmental pollution and there is a considerable emphasis on the recovery and recycling of food by-products and wastes. In this study, we focused on the exploitation of olive pomace as functional ingredient in biscuits and bread. Standard and enriched bakery products were made using different flours and fermentation protocols. After characterization, they were in vitro digested and used for supplementation of intestinal cells (Caco-2), which underwent exogenous inflammation. The enrichment caused a significant increase in the phenolic content in all products, particularly in the sourdough fermented ones. Sourdough fermentation also increased tocol concentration. The increased concentration of bioactive molecules did not reflect the anti-inflammatory effect, which was modulated by the baking procedure. Conventionally fermented bread enriched with 4% pomace and sourdough fermented, not-enriched bread had the greatest anti-inflammatory effect, significantly reducing IL-8 secretion in Caco-2 cells. The cell metabolome was modified only after supplementation with sourdough fermented bread enriched with 4% pomace, probably due to the high concentration of tocopherol that acted synergistically with polyphenols. Our data highlight that changes in chemical composition cannot predict changes in functionality. It is conceivable that matrices (including enrichment) and processing differently modulated bioactive bioaccessibility, and consequently functionality.